THE EFFECT OF GIVING DATES ON INCREASING HEMOGLOBIN LEVELS IN PREGNANT WOMEN AT PMB LASMI HANDAYANI BANDAR AGUNG, EAST LAMPUNG DISTRICT - Nurullita, Claudia Ratih; Yuningsih, Sukarni Setya (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background Decreased Hemoglobin levels are a major health problem in pregnant women. World Health Organization (WHO) states that globally more than 20% of pregnant women suffer from anemia throughout the world (WHO, 2019). Basic health research data (Riskesdas) shows that the incidence of anemia in pregnant women in Indonesia is still quite high, namely 37.1% in 2013 and rose to 47.9% in 2018 (Ministry of Health of the Republic of Indonesia, 2018). Data from the Lampung Provincial Health Service, in 2018 the prevalence of anemia reached 22.4% of 6,200 pregnant women, in 2019 it reached 20.7% of 5,800 pregnant women and in 2020 the prevalence of anemia increased again to 23.2% from 6,230 pregnant women, while the incidence of anemia in pregnant women in Pringsewu Regency was 27.8% in 2020 (Lampung Province Health Office Profile, 2021). Purpose of Writing To know The effect of giving dates on increasing hemoglobin levels in pregnant women at PMB Lasmi Handayani Bandar Agung, East Lampung Regency. Research methods The population used in this research is Quasy quasi-experimentPregnant women in third trimester and second trimester with anemia in PMB Lasmi Handayani Bandar Agung East Lampung Regency in the period December 2023 to January 2024 as many as 38 respondents. The number of samples in this research was 38 respondents.The sampling technique used in this research is T Total Sampling. Analyze data using analysis univariate and bivariate analysis use T-test Independent. Research result Statistical test results with T-test Independent shows that There is p The effect of giving dates on increasing hemoglobin levels in pregnant women at PMB Lasmi Handayani Bandar Agung, East Lampung Regency with a p-value of 0.000. Conclusions and recommendations It is hoped that future researchers can develop research by using different methods or research plans in providing health education to pregnant women about complementary management that can be given to pregnant women with anemia.